Host MicroRNA hsa-miR-494-3p Promotes EV71 Replication by Directly Targeting PTEN - Qing Zhao; Yuan Xiong; Jingru Xu; Shuang Chen; Pu Li; Yong Huang; Yunying Wang; Wei-Xian Chen; Bo Wang (Frontiers in Cellular and Infection Microbiology, 2018)
Many cellular processes are driven by spatially and temporally regulated microRNAs (miRNAs)-dependent signaling events. Substantial evidence collected over the years indicates that miRNAs are pivotal regulators that contribute to the initiation and development of EV71-related disorders. Importantly, so far, no clinical trial has been undertaken to address the effect of miRNAs on EV71-related diseases. In this study, we show that EV71 infection results in up-regulation of hsa-miR-494-3p levels, and that EV71-induced hsa-miR-494-3p impacts PI3K/Akt signaling pathway by targeting PTEN. However, very little is known about the relationship between hsa-miR-494-3p and EV71 infection. The overall goal of the study is to get a better insight into whether or not hsa-miR-494-3p is involved in the EV71 infection. We found that the EV71 infection induces cellular apoptosis, and that this process can be counteracted by the over-expression of hsa-miR-494-3p mimics. We also present evidence that cell lines deficient in hsa-miR-494-3p are more sensitive to EV71-induced cell death than the corresponding control cells. Collectively, these findings confirm and extend the pervious observation suggesting that disturbances in miRNAs expression can influence EV71 propagation. In addition, they lend strong support to the ideas that hsa-miR-494-3p-mediated signaling pathway plays an important role in the EV71 replication, and that this may have profound implications on our views on EV71-related diseases.